Rosa - Giovanni, Nikki; Collier, Bryan (New York : Henry Holt, 2005)
This book is an account of Rosa Parks and her refusal to give up her seat on a city bus, an event that changed our history.
K-3
900
Reading Counts RC
Accelerated Reader AR
Keywords: Parks, Rosa, -- 1913-2005.; Civil rights -- United States -- Biography